TAMAN PENDIDIKAN AL-QUR’AN SEBAGAI SARANA PEMBINAAN MORAL ANAK DI ERA DIGITAL : ANALISIS PERSEPSI WALI SANTRI TPA AR RAHMAN - Eka Fauziah, Wina; Iqbal Amar Muzaki; Yadi Fahmi Arifudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The decline of moral values among children has become a concerning issue in the modern era, particularly with the rapid development of digital technology. This condition requires efforts to strengthen character education from an early age through educational processes that instill religious and moral values. The Qur’anic Learning Center, commonly known as Taman Pendidikan Al-Qur’an (TPA), as a non-formal Islamic educational institution, plays a strategic role in shaping children's character through Qur’anic learning, the cultivation of moral values, and the habituation of religious practices in daily life. This study aims to analyze the role of TPA in shaping children's character as an effort to overcome moral decline. The research employs a qualitative approach using literature review and observation of learning activities in TPA. The findings indicate that TPA contributes significantly to the development of children’s moral and religious values, fostering discipline, responsibility, and behavior aligned with Islamic teachings. Furthermore, the effectiveness of character building through TPA is influenced by the support of parents, community, and a conducive environment. Therefore, TPA plays a crucial role in shaping children's character and serves as an alternative solution to address moral decline in society.